Enzymatic Degradation of Hyperbranched Polyesters - Mallepally, Rajendar Reddy; Smirnova, Irina; Arlt, Wolfgang; Seiler, Matthias; Klee-Laquai, Saskia K.; Hills, Geoffrey (Journal of Applied Polymer Science, 2009)
In this work, the enzyme-catalyzed degradation of hyperbranched polyesters (HBPEs) was investigated. Enzymatic degradation experiments were performed in a phosphate buffer in the presence of the lipases Candida cylindracea, Pseudomonas cepacia, Novozym 388, Amano CE, Lipomod 34P, and Cal-B, whereas control experiments were performed in the same system without lipases. The extent of polymer degradation was determined by quantification of the released free fatty acids by gas chromatography. The influence of the alkane chain length and the number of alkane chain end groups on the lipase-catalyzed hydrolysis of esterified HBPEs was investigated systematically. It was found that the increase in file alkane chain length of the end groups diminished the enzymatic degradation of the polymer, whereas the number of end groups had no influence oil the degradation rate. The effect of temperature oil the rate of degradation was also described. Surface morphological changes that occurred during the degradation were assessed with reflected electron microscopy. The changes in the crystallinity of the polymers after they were subjected to degradation were qualitatively determined with differential scanning calorimetry through the quantification Of the enthalpy of melting. The enthalpy of melting of one HBPE sample increased from 79 to 90 and 94 J/g with and without the action of Lipomod 34P, respectively, in 7 days, showing the changes in the crystallinity of the polymer. The results prove that modified HBPEs are an important new class of biodegradable materials with a predictable degradation mechanism, and the degradation can be adjusted oil the basis of the molecular engineering. (C) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 112: 1873-1881, 2009
Keywords: biodegradable; enzymes; hyperbranched; polyesters